Simulation of ship Speed and Direction by using TOPSAR Data - Marghany , Maged; Ibrahim , Zelina; Mohamed , Mohd Ibrahim; Mansor , Shattri (2000)
TOPSAR polarized data have many potential applications in coastal waters. One of the most important applications is in ship detection. Ship detection is an important aspect of marine traffic navigation. The main objective of this study is to establish speed and direction of ship movement. The first model used is based on the Doppler shift effect between sensor and target movement. The second model is based on the relationship between wavelength generated by ship and ship velocity. The statistical analysis of application of the two models has shown a significant correlation indicating high accuracy for ship detection and movement. The work shows that TOPSAR polarized data have the potential for monitoring ship speed and direction. The integration of 2-DFFT with the Doppler frequency shift model has proven useful in identifying the location and speed of the ship in coastal waters.